Prevalence of recurrent wheezing and its risk factors - Assis, Elisangela Vilar de; De Sousa, Milena Nunes Alves; Feitosa, Ankilma do Nascimento Andrade; De Souza, Ana Cecília Amorim; Leitão, Pablo de Almeida; Quental, Ocilma Barros de; Isidório, Ubiraidys de Andrade; Abreu, Luiz Carlos de; Valenti, Vitor Engrácia [UNESP] (My University, 2014)
Objective: analyze the prevalence of recurrent wheezing and its risk factors. Method: systematic literature review, guided by the research question what is the prevalence of recurrent wheezing and its risk factors?. The search was performed in the databases MedLine and LILACS, in April and May 2013. The inclusion criteria were: scientific study, fully available, published between 2002 and 2013, with free access. Results: wheezing presents a higher prevalence in developing countries, possibly due to poor socioeconomic conditions. Among its risk factors, we find heredity, mother's education level, attendance of day nursery, smoking during pregnancy, breastfeeding for < 3 months, animals in the household of children, among others. Conclusion: in Latin America, the prevalence of wheezing shows to be high and the use of non-standardized instruments hampers its treatment.
Keywords: Childhood wheezing; Recurrent wheezing; Wheezing